Radical thiol-yne chemistry on diphenylacetylene: Selective and quantitative addition enabling the synthesis of hyperbranched poly(vinyl sulfide)s - Poetzsch, Robert; Komber, Hartmut; Stahl, Brian C.; Hawker, Craig J.; Voit, Brigitte (Macromolecular Rapid Communications, 2013)
A powerful variation of traditional radical thiol-yne reaction with diphenylacetylene (DPA)-based starting materials leading to the quantitative and selective formation of the corresponding vinyl sulfides is reported. A variety of different thiols are shown to undergo reaction with DPA and the influence of their structure on reactivity is studied. The results obtained from the model reactions are then used to guide the efficient synthesis of hyperbranched poly(vinyl sulfide) (hb-PVS) systems by employing a dithiol and a trialkyne in an A2 + B3 approach. The polymers obtained show excellent solubility in common organic solvents and exhibit high refractive indices (e.g., 1.70 at 589 nm). The combined ease of processability and potential for cross-linking make these materials very interesting for applications, such as coatings for optical devices. The selective mono-addition thiol-yne reaction on DPA serves not only as a synthetic method for the preparation of PVS but could also be applied to the general modification of acetylene-containing materials. A versatile variant on traditional thiol-yne chemistry is demonstrated by the selective radical mono-addition of different thiols with diphenylacetylene (DPA) derivatives to form the corresponding vinyl sulfide. The results are extended to polymer synthesis enabling the preparation of hyperbranched poly(vinyl sulfide) (hb-PVS) by an A2 + B3 approach, yielding materials with excellent solubility and high refractive indices (1.70 at 589 nm) suitable for coating applications in optical devices © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: alkyne; high refractive index; hyperbranched; polyvinylsulfide; thiol; thiol-yne